RELATIONSHIP BETWEEN INDIVIDUAL CHARACTERISTICS AND WORK STRESS WITH NURSE PERFORMANCE DURING THE COVID-19 PANDEMIC IN HOSPITAL X - Puji, Lela Kania Rahsa; Kasumawati, Frida; Ratnaningtyas, Tri Okta; Hasanah, Nur; Fajrin, Erlin Vinita (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2023)
ABSTRACTDuring the pandemic research conducted in 8 islands in Indonesia stated that, health workers in Indonesia who experience stress by 55%, very heavy stress levels 0.8%, and mild stress as much as 34.5%.  This is due to the fear of being infected, the long workload, and the lack of PPE.  The purpose of this study is to find out the relationship between individual characteristics and work stress on nurse performance during the Covid-19 pandemic. Is quantitative research that uses primary data (questionnaire through google form) and uses cross sectional research methods with the aim of knowing the relationship between independent variables and dependent variables. The sample number was 126 nurses at X Hospital. From the results of the study obtained that work stress during the Covid-19 pandemic, nurses who experienced moderate work stress were accompanied by moderate performance as many as 62 respondents (49,2%), while respondents who experienced severe stress accompanied by moderate performance as many as 30 respondents (23,8%). The results of the statistical test obtained a value (p-value = 0.035, α: 0.05) then it can be concluded that there is a significant relationship between work stress (during the Covid-19 pandemic) and nurse performance during the Covid-19 pandemic. From the results of this study, it is hoped that institutions can pay more attention to the health of health workers, especially nurses, both physical, psychic and work environment so that nurses remain at optimal performance. ABSTRAKSelama pandemi penelitian yang dilakukan di 8 kepulauan di Indonesia menyatakan bahwa, tenaga kesehatan di Indonesia yang mengalami stres sebesar 55%, tingkat stres sangat berat 0,8%, dan stres ringan sebanyak 34,5%. Hal ini disebabkan karena ketakutan akan terinfeksi, beban jam kerja yang panjang, dan kurangnya APD. Tujuan penelitian ini adalah untuk mengetahui hubungan antara karakteristik individu dan stres kerja terhadap kinerja perawat di masa pandemi covid-19. Merupakan penelitian kuantitatif yang menggunakan data primer (kuesioner melalui google form) dan memakai metode penelitian cross sectional dengan tujuan untuk mengetahui hubungan antara variabel independen dengan variabel dependen. Jumlah sampel sebanyak 126 perawat di Rumah Sakit X. Dari hasil penelitian diperoleh bahwa stres kerja selama pandemi covid-19, perawat yang mengalami stres kerja sedang disertai dengan kinerja sedang sebanyak 62 responden (49,2%), sedangkan responden yang mengalami stres berat disertai dengan kinerja sedang sebanyak 30 responden (23,8%). Hasil uji statistik diperoleh nilai (p-value=0,035, α: 0,05) maka dapat disimpulkan ada hubungan yang signifikan antara stres kerja (selama pandemi covid-19) terhadap kinerja perawat dimasa pandemi covid-19. Dari hasil penelitian ini diharapkan institusi dapat lebih memperhatikan kesehatan para tenaga kesehatan khususnya perawat, baik fisik, psikis dan lingkungan kerja agar para perawat tetap berada pada kinerja yang optimal.